Binocular Function under Unusual Light Condition: A Cross-Sectional Study - Monireh Mahjoob; Batool Haghighi (Vesnu Publications, 2020)
Introduction: Glare is an unusual light condition that may alter the visual function. The aim of this study is to evaluate the effect of glare on binocular evaluation tests.Materials and Methods: In this cross sectional study, 44 healthy students of Zahedan University of Medical Sciences, Zahedan, Iran were selected. Binocular evaluation tests were direct tests such as cover test, near point of convergence, and fusional reserves, and the indirect tests included binocular accommodative facility and relative accommodation, which were performed in the standard and glare light conditions. Statistical analysis was performed using the paired sample t-test .Results: The findings showed the negative fusional reserves at blur, break, and recovery point was significantly different in the two light conditions (P < 0.049). Moreover, other tests of binocular evaluation had no significant difference under the glare and normal light conditions (P > 0.050).Conclusion: Given this study, glare seems to have a negative impact on negative fusional reserves. Therefore, given the limited range of negative fusional reserve, effect of unusual lighting condition should be considered, especially in people with intermittent esotropia or decompensated esophoria.